Benefits of switching from intravenous to subcutaneous daratumumab: Perspectives from UK healthcare providers - Cook, Gordon; Ashcroft, John; Fernandez, Mariana; Henshaw, Sarah; Khalaf, Zeyad; Pratt, Guy; Tailor, Anish; Rabin, Neil (Frontiers in Oncology, 2023)
Daratumumab is a CD38-directed monoclonal antibody indicated to treat multiple myeloma (MM). Daratumumab was initially administered intravenously (IV), subsequently a subcutaneous (SC) formulation was developed to increase convenience of administration. The UK was an early adopter of SC daratumumab and, as such, this report provides consensus recommendations from a group of UK MM experts, with the aim of facilitating the transition from IV to SC daratumumab for other European healthcare providers. The switch from IV to SC daratumumab has been beneficial to patients and healthcare providers, as it simplifies treatment, reduces pressure on hospitals and can improve patients’ quality of life.